Atrial fibrillation among Russian men and women aged 55 years and older: prevalence, mortality, and associations with biomarkers in a population-based study - Shkolnikova, Maria A. (J Geriatr Cardiol, 2020)
OBJECTIVE: To examine the prevalence of atrial fibrillation (AF), its impacts on cardiovascular disease (CVD) and all-cause mortality, and the associations between AF and inflammatory and serum biomarkers in a population-based sample of Muscovites. METHODS: The study is a secondary analysis of data from the Stress, Aging and Health in Russia (SAHR) survey that includes information on 1800 individuals with an average age of 68.5 years at baseline, and on their subsequent mortality during 7.4 years on average. AF is detected by 12-lead electrocardiogram (ECG) and 24-hour Holter monitoring. The statistical analysis includes proportional hazard and logistic regression models. RESULTS: Of the 1732 participants with relevant Holter data, AF was detected in 100 (74 by ECG and Holter, 26 by Holter only). The prevalence of AF was 5.8% for men and 7.4% for women. The fully adjusted model showed strongly elevated hazard of CVD and all-cause mortality in men and women with long non-self-limiting AF (LAF). LAF was found to be negatively associated with elevated total and low-density lipoprotein cholesterol and to be positively associated with elevated markers of inflammation in women. CONCLUSIONS: The study assessed for the first time the prevalence and the risks of death related to AF among older Russians. LAF was shown to be a strong and independent predictor of CVD and all-cause mortality. AF is unlikely to contribute to the large excess male mortality in Russia. The finding that one-quarter of AF cases were detected only by Holter monitoring demonstrates the usefulness of diagnostics with prolonged ECG registration.